2011
DOI: 10.1249/mss.0b013e31820a7c12
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training in Type 2 Diabetes with Inspiratory Muscle Weakness

Abstract: Patients with type 2 diabetes may frequently present inspiratory muscle weakness. In these patients, IMT improves inspiratory muscle function with no consequences in functional capacity or autonomic modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 42 publications
5
37
2
8
Order By: Relevance
“…Studies have shown that inspiratory muscle training improves inspiratory muscle strength in clinical conditions such as type 2 diabetes (Corrêa et al, 2011), heart failure (Mello et al, 2012) and hypertension Tenorio (Ferreira et al, 2013). However, the protocol of training in these studies ranged between 8 and 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inspiratory muscle training improves inspiratory muscle strength in clinical conditions such as type 2 diabetes (Corrêa et al, 2011), heart failure (Mello et al, 2012) and hypertension Tenorio (Ferreira et al, 2013). However, the protocol of training in these studies ranged between 8 and 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…7 A capacidade funcional, verificada por TC6min, PImáx e PEmáx, mostrou-se adequada, com exceção da força muscular expiratória, a qual se apresentou abaixo de 70% do previsto. Diferentemente do encontrado na presente investigação, estudos apontaram que pacientes com DM2 apresentam diminuição da força muscular inspiratória (PImáx) 16,26 relacionada com redução dos volumes pulmonares e qualidade do controle metabólico. 26 Corrêa e cols.…”
Section: Discussionunclassified
“…26 Corrêa e cols. 16 observaram prevalência de fraqueza muscular inspiratória de 29% sobre uma amostra de 148 pacientes com DM2, sendo o treinamento muscular inspiratório benéfico na reversão da fraqueza e resistência muscular, sem efeitos sobre a capacidade funcional e a variabilidade da frequência cardíaca dos pacientes. As DCNT podem influenciar negativamente na capacidade funcional dos indivíduos, ocasionando alterações no desempenho de suas atividades de vida diária.…”
Section: Discussionunclassified
See 2 more Smart Citations